Pengaruh Saham Syariah Oblgasi Syariah dan Reksadna Syariah yang Terdaftar di Otoritas Jasa Keuangan Terhadap Pertumbuhan Ekonomi Indonesia Periode 2016-2020 - Putri Sari Amanda; Mario Aldo Tria Abidin; Jalaluddin Jalaluddin (Ma'soem University, 2021)
Based on the results of the initial research, that the background of this research is fluctuating data and the existence of a gap between theories between Sharia Stocks, Sharia Bonds, Sharia Mutual Funds registered with the Financial Services Authority (OJK) in Economic Growth for the 2016-2020 period. This study aims to determine the effect of sharia shares on economic growth, to determine the effect of sharia bonds on economic growth, to determine the effect of sharia mutual funds on economic growth in Indonesia, and to determine how the influence of sharia shares, sharia bonds, and sharia mutual funds on economic growth. The object of research used is the financial reports on Islamic stocks, Islamic bonds and Islamic mutual funds in the OJK financial statements for the quarterly period and economic growth in the BPS quarterly reports. The type of research is quantitative associative, the type of data is secondary data and uses data collection techniques in the form of documentation and literature study, with population data from OJK and BPS, while the sample used in this study is quarterly data on Islamic stocks, Islamic bonds, Islamic mutual funds. , and economic growth from 2016-2020. The results of this study indicate that there is no effect of Islamic stocks on economic growth with a KD value of 0.5% and tcount < ttable (0.303 < 2.110), there is a negative effect between Islamic bonds on economic growth with KD 20.31% and tcount > ttable (-2.141 > 2.110), and there is no influence between sharia mutual funds on economic growth with KD 0.16% and tcount < ttable (0.172 < 2.110), and simultaneously there is no effect between sharia shares, sharia bonds, sharia mutual funds on growth economy with the coefficient of determination of 23% and the results of the f test > ftable > ftable (1,593 > 3,24).